Anthroponyms in the onomastic space kumyk folklore tales - Ruganiyat A., Musayeva (Kavkazologiya, 2025)
The topic focuses on anthroponyms used in folklore texts. The work's goal is to investigate hu-man names in Kumyk folk story texts, identifying their semantic aspects, frequency of usage, and role and function as linguistic methods that contribute to the development of creative pictures. The research examines the composition and organization of the anthroponymic realm, revealing the characteristics of how the Kumyk onyms function.